Assessing the Role of Circular Economy in Strengthening Regional Economic Resilience in the Post-Pandemic Context - Ali Hardana; Claudia; Vanesa Yolanda (CV. Get Press Indonesia, 2025)
The COVID-19 pandemic exposed vulnerabilities in linear economic models, highlighting the need for resilience at regional levels. This study examines how the circular economy (CE) can enhance regional economic resilience post-pandemic through waste reduction, resource reuse, and innovation. Using a systematic literature review and mixed-methods analysis of peer-reviewed sources and policy reports, findings show CE reduces reliance on fragile supply chains, lowers costs, and creates green jobs. Success depends on adaptive local policies and multi-stakeholder collaboration, with digital technologies like Industry 4.0 playing a key role. Research gaps include limited long-term data and contextual studies, indicating a need for future multidisciplinary research. The findings support CE as a vital strategy for sustainable economic recovery and resilience.